Sosialisasi Manajemen Kesehatan Kambing Perah serta Pengaruhnya terhadap Kualitas Susu pada Peternak Kambing Perah di Kecamatan Ampelgading dan Tirtoyudo Kabupaten Malang - Mira Fatmawati; Woro HAmbarrukmi; Lucia Endah Sukesi; Masdiana Cendrakasih Padaga (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Goat's milk is a food of animal origin that is easily damaged and requires handling after the milking process. Ampelgading and Tirtoyudo sub-districts are areas in Malang Regency where some of the population are dairy goat breeders. This community service aims to provide socialization and education on good animal health management so that it can improve the quality of goat milk. The activity began with collecting farmer data and analyzing the situation of dairy goat farming. The socialization method was carried out by conducting focus group discussions about knowledge of animal health management and checking the quality of goat milk. Milk composition testing uses Lactoscan, while organoleptic testing is based on Indonesian National Standard 01-2346-2006 concerning organoleptic and sensory testing instructions. The results of community service show that the quality of dairy goat milk in Ampelgading and Tirtoyudo Districts is premium based on the Thailand Agriculture Standard 2008. The results of the organoleptic test of goat milk have remained the same based on SNI 3141-1-2011 regarding the quality of fresh milk. The results of this goat milk quality test can be used as a basis for farmers to improve livestock management and milking. Through this activity, farmers can implement good livestock health management so that the quality of goat milk and the selling price increase. This activity will encourage young farmers to be more interested in becoming dairy goat breeders who have high economic prospects and contribute to increasing goat milk productivity. Apart from that, this activity can improve the welfare of farmers by improving the quality of goat milk with higher selling power.